TINDAK PIDANA PENCUCIAN UANG DAN KEKELIRUAN MEMAHAMI EXTRAORDINARY CRIME - Gusti Anom Wijaya (CV Widina Media Utama, 2026)
Money laundering is a crime involving attempts to conceal or disguise the proceeds of a criminal act so that they appear to come from legitimate activities. In practice, money laundering is often viewed as an extraordinary crime because it is closely linked to various serious criminal offenses such as corruption, narcotics, and other organized crimes. This study employs a normative legal research method using a legislative approach and literature review to analyze the characteristics of “extraordinary crimes” and the position of ML within that classification. The results show that although TPPU is a serious crime characterized by high complexity and the potential to disrupt economic stability, it does not automatically meet all the characteristics of an “extraordinary crime.” This is because not all TPPU cases have systemic impacts on the state, their handling still relies on general criminal law mechanisms, and the primary focus is more oriented toward asset tracing and recovery. Therefore, law enforcement against money laundering must be carried out firmly and effectively without disregarding the principles of the rule of law, the protection of human rights, and due process of law. The novelty of this study lies in its assertion that money laundering cannot automatically be classified as an “extraordinary crime,” but should instead be categorized as a “serious crime” that requires robust law enforcement while upholding the principle of due process of law. This finding provides a conceptual foundation for the development of more proportionate criminal justice policies in addressing money laundering in Indonesia. ABSTRAKTindak Pidana Pencucian Uang (TPPU) merupakan kejahatan yang berkaitan dengan upaya menyembunyikan atau menyamarkan hasil tindak pidana agar tampak berasal dari kegiatan yang sah. Dalam praktiknya, TPPU sering dipandang sebagai kejahatan luar biasa karena memiliki hubungan erat dengan berbagai tindak pidana serius seperti korupsi, narkotika, dan kejahatan terorganisir lainnya. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan kajian literatur untuk menganalisis karakteristik extraordinary crime serta posisi TPPU dalam klasifikasi tersebut. Hasil penelitian menunjukkan bahwa meskipun TPPU merupakan kejahatan serius (serious crime) yang memiliki kompleksitas tinggi dan berpotensi mengganggu stabilitas ekonomi, TPPU tidak secara otomatis memenuhi seluruh karakteristik Extraordinary Crime. Hal ini karena tidak semua kasus TPPU menimbulkan dampak sistemik terhadap negara, penanganannya masih menggunakan mekanisme hukum pidana umum, serta fokus utamanya lebih berorientasi pada pelacakan dan pemulihan aset. Oleh karena itu, penegakan hukum terhadap TPPU perlu dilakukan secara tegas dan efektif tanpa mengabaikan prinsip negara hukum, perlindungan hak asasi manusia, dan asas due process of law. Kebaruan penelitian ini terletak pada penegasan bahwa TPPU tidak dapat secara otomatis diklasifikasikan sebagai extraordinary crime, melainkan lebih tepat diposisikan sebagai serious crime yang memerlukan penegakan hukum yang kuat dengan tetap menjunjung prinsip due process of law. Temuan ini memberikan dasar konseptual bagi pengembangan kebijakan hukum pidana yang lebih proporsional dalam penanganan TPPU di Indonesia. Money Laundering (ML) is a crime related to efforts to conceal or disguise the proceeds of criminal activities so that they appear to originate from legitimate sources. In practice, money laundering is often regarded as an extraordinary crime because of its close connection with various serious offenses such as corruption, narcotics crimes, and other forms of organized crime. This study employs a normative legal research method using statutory and literature approaches to analyze the characteristics of extraordinary crimes and the position of money laundering within such classification. The findings indicate that although money laundering constitutes a serious crime with high complexity and the potential to disrupt economic stability, it does not automatically fulfill all characteristics of an extraordinary crime. This is because not all money laundering cases create systemic impacts on the state, its enforcement still relies on general criminal law mechanisms, and its primary focus is more oriented toward asset tracing and asset recovery. Therefore, law enforcement against money laundering must be carried out firmly and effectively without disregarding the principles of the rule of law, the protection of human rights, and the principle of due process of law.Money Laundering (ML) is a crime related to efforts to conceal or disguise the proceeds of criminal activities so that they appear to originate from legitimate sources. In practice, money laundering is often regarded as an extraordinary crime because of its close connection with various serious offenses such as corruption, narcotics crimes, and other forms of organized crime. This study employs a normative legal research method using statutory and literature approaches to analyze the characteristics of extraordinary crimes and the position of money laundering within such classification. The findings indicate that although money laundering constitutes a serious crime with high complexity and the potential to disrupt economic stability, it does not automatically fulfill all characteristics of an extraordinary crime. This is because not all money laundering cases create systemic impacts on the state, its enforcement still relies on general criminal law mechanisms, and its primary focus is more oriented toward asset tracing and asset recovery. Therefore, law enforcement against money laundering must be carried out firmly and effectively without disregarding the principles of the rule of law, the protection of human rights, and the principle of due process of law.Money Laundering (ML) is a crime related to efforts to conceal or disguise the proceeds of criminal activities so that they appear to originate from legitimate sources. In practice, money laundering is often regarded as an extraordinary crime because of its close connection with various serious offenses such as corruption, narcotics crimes, and other forms of organized crime. This study employs a normative legal research method using statutory and literature approaches to analyze the characteristics of extraordinary crimes and the position of money laundering within such classification. The findings indicate that although money laundering constitutes a serious crime with high complexity and the potential to disrupt economic stability, it does not automatically fulfill all characteristics of an extraordinary crime. This is because not all money laundering cases create systemic impacts on the state, its enforcement still relies on general criminal law mechanisms, and its primary focus is more oriented toward asset tracing and asset recovery. Therefore, law enforcement against money laundering must be carried out firmly and effectively without disregarding the principles of the rule of law, the protection of human rights, and the principle of due process of law.Money Laundering is a crime related to efforts to conceal or disguise the proceeds of criminal activities so that they appear to originate from legitimate sources. In practice, money laundering is often regarded as an extraordinary crime because of its close connection with various serious offenses such as corruption, narcotics crimes, and other forms of organized crime. This study employs a normative legal research method using statutory and literature approaches to analyze the characteristics of extraordinary crimes and the position of money laundering within such classification. The findings indicate that although money laundering constitutes a serious crime with high complexity and the potential to disrupt economic stability, it does not automatically fulfill all characteristics of an extraordinary crime. This is because not all money laundering cases create systemic impacts on the state, its enforcement still relies on general criminal law mechanisms, and its primary focus is more oriented toward asset tracing and asset recovery. Therefore, law enforcement against money laundering must be carried out firmly and effectively without disregarding the principles of the rule of law, the protection of human rights, and the principle of due process of law.